VALIDATION OF THE SUBJECTIVE GLOBAL ASSESSMENT AND MALNUTRITION INFLAMMATION SCORE TRANSLATED TO PORTUGUESE FOR ELDERLY PATIENTS ON HEMODIALYSIS. - Renata Fetter; Fernanda Bigogno; Juliana Rodrigues; Fernando Lamarca; Ana Lúcia Pereira; Laís Morgado (The Korean Society of Nephrology, 2012)
We aimed to validate the translation of the 7 point subjective global assessment (7 p-SGA) and malnutrition inflammation score (MIS) from English to Portuguese to be applied for elderly patients on hemodialysis (HD). For the translation, the back-translation method was used. First, two independent bilinguals renal dietitians (Portuguese native speakers) worked independently to translate the 7 p-SGA and MIS to Portuguese. After that, the final version was back translated to English by a bilingual English teacher (Portuguese native speaker). In order to investigate the conceptual and semantic equivalence of the translated version, a renal dietitian (English native speaker) compared each item of the original English version of the 7 p-SGA and MIS to the back translated English version by rating the similarity between both questionnaires from 1 to 100 (being 100 the highest degree of similarity). The degree of similarity was 96.8 ±7.8 for 7p-SGA and 99.6 ±1.4 for MIS, indicating that the Portuguese versions had equivalent meaning to the original English version. We then performed the validation of the Portuguese version by assessing the concurrent concordance of both nutritional composite indices with objective methods (BMI, body fat %, phase angle, handgrip strength and albumin) in 64 elderly patients on HD (male 72%; 70±3 years old). The 7p-SGA was rated as well nourished (score 7-6; n= 30); mildly to moderately malnourished (5-3; n= 34) and severely malnourished (2-1; no patient). The MIS was rated as normal nutrition (score: 0-5; n= 12); mild malnutrition (6-10; n= 38), and moderate-to-severe malnutrition (≥11; n= 14). Among the objective methods, only body fat % differed (P<0.05) between well-nourished and malnourished patients for the 7p-SGA, and for MIS, the same was observed only for body fat % and phase angle. In conclusion, these preliminary results suggest that for elderly patients on HD, the scores proposed by the 7p-SGA and MIS for screening patients with protein energy wasting should be reviewed.